(untitled) (American Journal of Islam and Society, 2006)
The masjid, better known in North America as the Islamic center, is the center of spiritual, social, educational, and, most recently, political activities of the American Muslim community. The masjid is also the place where Muslims of diverse cultural and ideological backgrounds meet and interact. The diversity of interpretations of Islamic sources and practices has created tensions, particularly in Islamic centers where the tendency is to impose strict interpretations about the appropriate place and role of Muslim women in the masjid and the community. An increasing number of young Muslim women complain of restrictive arrangements and practices, impeding their ability to fully participate in educational and social programs. Many masjids today restrict the main prayer hall to men and assign women to secluded quarters. Women are asking out loud: “Is this the place Islam assigns for us, or is it the imposition of cultural traditions?” Some have even gone to the other extreme of rejecting all traditions and discarding all limits ...